Evaluation of the biological activity of different 4-aminoquinolines for the development of new drugs against painful and inflammatory disorders - Geraldo José da Silva Neto; Suellen Maria Albuquerque da Silva; Daniele Costa Souza Barros; Alyne Almeida de Lima; Max Denisson Maurício Viana; Magna Suzana Alexandre Moreira; Mario Roberto Meneghetti; Eliane Aparecida Campesatto (Elsevier, 2023)
The potential biological properties of four 4-aminoquinoline derivatives (1-4) have been previously demonstrated. However, the evaluation of important aspects of their toxicity, anti-inflammatory, and antinociceptive activities has not been described. Here, we report other pharmacological properties of 1-4 using classic in vivo models of pain and inflammation. Preliminary toxicity tests revealed the narrow therapeutic window of the compounds, and the doses for biological tests were chosen after median lethal dose (LD50) determination. Then, the formalin-induced nociception test was used for screening. The antinociceptive and anti-inflammatory potentials were observed only in the inflammatory phase among 1-3 at the highest administered dose (50 mg/kg, p.o.). This response pattern was confirmed for all compounds in the acute inflammation model of zymosan-induced peritonitis. The intriguing lack of activity in the first phase of the formalin test led us to explore other pathways through other methods. The derivatives exhibited antinociceptive activity in peripheral and central components of pain in different patterns among models. In the acetic acid-induced writhing test, oral pretreatment with 1 and 2 significantly reduced painful behavior. Glutamate-mediated nociceptive induction was attenuated by 1 and 3. Under thermal stimulation, all compounds produced antinociception in the hot plate test in mice, confirming a centrally mediated action. Moreover, 1-3 at antinociceptive and anti-inflammatory doses did not affect the motor performance in mice in the rotarod test, thus validating the data. This work is the first report of these activities for 1-3. Because they are chloroquine analogs, these compounds represent ideal prototypes of antinociceptive and anti-inflammatory drugs that are able to induce peripheral and central effects on pain and inflammation pathways. Further studies are needed for pharmacodynamic characterizations.